Prediction of the Abnormal Properties in Monolayer α‐AlxGa2−xO3. Issue 11 (16th September 2020) - Wei, Yidan; Liu, Chaoming; Tsai, Hsu‐Sheng; Zhang, Yanqing; Qi, Chunhua; Ma, Guoliang; Wang, Tianqi; Huo, Mingxue
Abstract: The present work based on the first principle and molecular dynamics calculations predicts the new 2D monolayers exfoliated from α‐Al x Ga2− x O3 with non‐van der Waals interactions. The huge differences in electronic, optical, and thermal performances have been observed between the new 2D monolayers and their bulk parents, and these properties can effectively be tuned by the ratio of Al and Ga. In particular, the thermal conductivity of monolayer α‐AlGaO3 is the highest among the 2D α‐Al x Ga2− x O3 phases. This calculation can be the basis for seeking the 2D α‐Al x Ga2− x O3 with machinability, suitable optical, and thermal performances during the design and development of flexible devices. Abstract : Among all of the monolayer α‐Al x Ga2− x O3 with different ratios of Al and Ga, the thermal conductivity roughly decreases with the x from 0 to 2, except for that of the monolayer α‐AlGaO3 which is the highest due to its longer phonon lifetime.